Patient Characteristics Predictive of Immediate and Delayed Word Recall Performance Following Adolescent Concussion - Wingerson, Mathew J; Wilson, Julie C; Seehusen, Corrine N; Walker, Gregory A; Howell, David R (International Journal of Sports Medicine, 2022)
Clinicians rely on objective concussion assessments that may be influenced by patient characteristics, creating difficulties in isolating the effect of concussion on patient function. The purpose of our study was to identify characteristics associated with performance on the Sport Concussion Assessment Tool 5th edition (SCAT5) 10-word recall test following adolescent concussion. We evaluated patients seen for care within 14 days of concussion (n=125; 15.2±1.6 years of age, range=11–18 years; 46% female; 6.9±3.4 days post-concussion). Patient demographic (age, sex, medical and concussion history, etc.), injury (timing of presentation, symptom severity, sport-type, etc.), and clinical test (Modified Balance Error Scoring System [mBESS], tandem gait) characteristics were assessed, in addition to SCAT5 immediate and delayed memory testing using the 10-word recall list. Immediate and delayed recall performance was significantly associated with concussion symptom burden and cognitive accuracy during tandem gait, although effect sizes were notably small. Specific variables such as age, sex, diagnosis of ADD/ADHD, and performance on other clinical assessments were not significantly associated with recall performance after controlling for covariates. Further, the 10-word recall list demonstrates specific advantages over previously used 5-word lists by way of decreased ceiling effects and reduced interference of inherent patient characteristics.
Keywords: mTBI; pediatric; memory; cognition; SCAT5; determinants